Long-term ovarian function in women treated with CHOP or CHOP plus etoposide for aggressive lymphoma - Meißner, Julia; Tichy, Diana; Katzke, Verena; Kühn, Thomas; Dietrich, Sascha; Schmitt, Tanja; Ziepert, Marita; Kuhnt, E.; Rixecker, T.; Zorn, Markus; Witzens-Harig, Mathias; Pfreundschuh, M.; et al. (Annals of oncology, 2015)
Background - Chemotherapy-associated ovarian damage comprises not only infertility, but also premature menopause. The latter has been reported as a consequence of alkylating chemotherapy for breast cancer or Hodgkin's lymphoma. In this study, we assessed the long-term impact of CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone)-like regimens on ovarian function in patients with aggressive non-Hodgkin lymphoma (NHL). - Patients and methods - Long-term survivors after CHOP or CHOP plus etoposide (CHOEP) treatment within the Mabthera International Trial or the NHL-B1 trial of the German NHL Study Group were requested to respond to a questionnaire and to consent to blood sampling for hormone assessment. - Results - A total of 46 of 81 contacted patients with a median age of 32.5 years at the time of enrolment into the aforementioned clinical trials responded to the questionnaire. The median follow-up after completion of treatment was 14 years. Last menstrual bleeding occurred significantly earlier in patients compared with the general population (47 versus 51 years, P < 0.0001). In comparison to the distribution of menopausal symptoms in the general population, the percentage of women with moderate or severe menopausal symptoms was increased. In 23 patients who agreed to participate in laboratory analyses, anti-Muller hormone as a marker of ovarian reserve was decreased when compared with correspondent age groups of the general population. - Conclusion - Although most female patients regain fertility after CHOP-like chemotherapy, late ovarian impairment occurs frequently. Therefore, awareness of such delayed side-effects at the time of counselling is of importance.
Gesehen am 12.06.2020